Reformer Pilates vs Mat Pilates and Muscle Mass: Current State of Knowledge - Śliwa, Zofia; Botto, Zofia; Krystek, Klaudia; Felisiak, Patrycja; Reizer, Barbara; Kowalczyk, Dominika; Ślazyk, Dominik Andrzej (Quality in Sport, 2026)
Pilates is widely implemented in sport, rehabilitation, and health-oriented exercise programs, with well-documented benefits for strength, flexibility, balance, and functional performance. However, its effectiveness in inducing skeletal muscle hypertrophy remains uncertain. This narrative review summarizes and critically evaluates the current state of knowledge regarding the effects of mat-based and reformer-based Pilates on muscle mass–related outcomes. Evidence from randomized controlled trials, comparative studies, and systematic reviews examining lean body mass, fat-free mass, appendicular lean mass, or muscle size was synthesized. Available findings indicate that clinically meaningful increases in muscle mass following Pilates training are inconsistent across populations and study designs. Mat Pilates generally demonstrates minimal effects on lean mass, while reformer Pilates is mechanistically better positioned to promote hypertrophy due to its capacity for external loading and progression; nevertheless, empirical support for this effect remains limited and heterogeneous. Overall, Pilates reliably improves strength and functional outcomes but does not consistently elicit robust muscle mass gains. Reformer Pilates may offer advantages over mat Pilates for muscle mass accretion when progressive resistance is emphasized, although further high-quality, hypertrophy-focused trials are required to clarify its role.